Tectonic Control of the Nanggulan Formation Based on Morphometric Analysis in Kulon Progo, Indonesia - Winarti Winarti; Emi Sukiyah; Ildrem Syafri; Andi Agus Nur (Indonesian Journal on Geoscience, 2022)
DOI:10.17014/ijog.9.2.147-157Outcrop of Nanggulan Formation, surrounded by Old Andesite Formation (OAF) in the eastern part of Kulon Progo Dome, is very limited. Tectonic control is interpreted as a contributing factor. Tectonic activity can be shown by a morphometric aspect. The research purpose was to calculate the valley floor - valley height ratio, stream gradient index, and drainage density of Nanggulan and Old Andesite Formations. The method used is field survey and Shuttle Radar Topography Mission analysis. The field survey focused on Clumprit, Klepu, and Kalisonggo Rivers. The total number of valley segments for the Nanggulan Formation is 223 with the valley length of 4.62 km, while OAF is 101 with a valley length of 3.55 km. SRTM analysis showed that the valley segment in OAF was 55, and valley length was 1.48 km. The valley floor - valley height ratio measured in the Nanggulan Formation is ten valleys and OAF is eight valleys. In Nanggulan Formation, the valley floor - valley height ratio value is from 1.00 to 5.46 (low uplift), whilst in OAF, the results vary: as 1.35 to 4.58 (low uplift), 0.59 (medium uplift), and 0.43 (high uplift). The stream gradient index value of the Nanggulan Formation is 460.47 (medium tectonic), while OAF is 723.84 (high tectonic). The drainage density value of the Nanggulan Formation is 10.35 km/km2 (very smooth landscape texture) and OAF is 10.35 km/km2 (somewhat smooth landscape texture). Morphometry proves that Nanggulan Formation tectonic activity is more active, causing the Nanggulan Formation to be exposed to the surface.